2017
DOI: 10.1111/1911-3846.12343
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Consequences of Perk Disclosure

Abstract: In December 2006, the SEC issued new rules requiring enhanced disclosure by public U.S. firms of perquisites granted to their executives. The rules applied to perquisites granted in fiscal year 2006 and thereafter. Because the rules were implemented quickly, the perks disclosed for 2006 reflect the arrangements firms made under prior disclosure rules: firms could not revise perks to reflect the new rules until 2007. For firms that disclose for the first time in 2006, we predict and find that perks decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…We argued earlier that the problem of managerial slack is particularly severe in China given its relatively weak financial disclosure system that creates substantial information asymmetry between management and shareholders. Recent studies in the US have indicated that enhanced disclosure rules imposed by Securities and Exchange Commission (SEC) in 2006 lead to disclosures of significantly larger amounts of perquisites and a substantial reduction in these discretionary expenses afterwards (Grinstein, Weinbaum, & Yehuda, 2017). We thereby suggest that imposing more extensive financial disclosure rules might be a reasonable policy direction to better constrain managerial value diversion and improve operational efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We argued earlier that the problem of managerial slack is particularly severe in China given its relatively weak financial disclosure system that creates substantial information asymmetry between management and shareholders. Recent studies in the US have indicated that enhanced disclosure rules imposed by Securities and Exchange Commission (SEC) in 2006 lead to disclosures of significantly larger amounts of perquisites and a substantial reduction in these discretionary expenses afterwards (Grinstein, Weinbaum, & Yehuda, 2017). We thereby suggest that imposing more extensive financial disclosure rules might be a reasonable policy direction to better constrain managerial value diversion and improve operational efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Few scholars, however, believe that CEO perquisites represent an efficient way to monitor or influence executives. Recent studies show that the relation between perks and short-run abnormal return is negative (Grinstein, Weinbaum, & Yehuda, 2011;Rajan & Wulf, 2006;Yermack, 2006;). Grinstein et al (2011), in particular, find that perks are positively related to CEO power and free cash flow, while negatively associated with a firm's growth opportunities.…”
Section: Management Perquisites Hypothesismentioning
confidence: 99%
“…Recent studies show that the relation between perks and short-run abnormal return is negative (Grinstein, Weinbaum, & Yehuda, 2011;Rajan & Wulf, 2006;Yermack, 2006;). Grinstein et al (2011), in particular, find that perks are positively related to CEO power and free cash flow, while negatively associated with a firm's growth opportunities. Baron (2009) similarly argues that managers could undertake CSR activities because of their own personal interests.…”
Section: Management Perquisites Hypothesismentioning
confidence: 99%
“…Yermack (2006) finds that the excessive use of corporate jets by executives appears to be viewed unfavorably by shareholders. Grinstein, Weinbaum, and Yehuda (2011) also find evidence that corporate perks are suboptimal for shareholders. Alternatively, Rajan and Wulf (2006) suggest that the use of corporate perks might be optimal in equilibrium.…”
Section: Introductionmentioning
confidence: 88%
“…Alternatively, Rajan and Wulf (2006) suggest that the use of corporate perks might be optimal in equilibrium. However, Yermack (2006), Rajan and Wulf (2006), and Grinstein et al (2011) all examine the use of corporate perks, which are an endogenous decision variable by the firm. Fortune's rankings are likely exogenous to any one firm, and the 1994 methodological change also allows the construction of a natural experiment.…”
Section: Introductionmentioning
confidence: 99%